Burden and risk factors of ambulatory or hospitalized CAP: A population based cohort study. (December 2016) - Kolditz, Martin; Tesch, Falko; Mocke, Luise; Höffken, Gert; Ewig, Santiago; Schmitt, Jochen
Abstract: Background: Data on incidence, risk factors and outcome of community-acquired pneumonia (CAP) including outpatients is sparse. Methods: We conducted a cohort study on 1.837.080 adults insured by a German statutory health insurance in 2010–2011. CAP was identified via ICD-10-GM codes, ambulatory cases were validated by antibiotic prescription within 7 days. Primary outcomes were incidence, hospitalisation and 30-day all-cause mortality. Evaluated risk factors included age, sex and comorbidities. Evaluation was done by multivariate regression analysis adjusting for these factors and health care utilization. Results: CAP incidence was 9.7 per 1000 person years, hospitalisation rate 46.5%, and 30-day mortality 12.9%. 30-day mortality of ambulatory cases was 5% (with 27% subsequently hospitalized for another diagnosis before death). 30-day mortality of hospitalized patients was 21.9%, but in-hospital mortality 17.2%. Risk factors for CAP included age, male sex and all evaluated comorbidities with highest risk for neurologic (OR 2.4), lung (OR 2.3) or immunosuppressive (OR 2.1) disease. Mortality risk was highest for neurologic (OR 2.3) and malignant (OR 2.0) disease. Conclusions: CAP constitutes a major burden in terms of incidence, morbidity and all-cause mortality in hospitalized and ambulatory patients. Interventions to raise awareness for disease impact also in ambulatory patients with risk factors are warranted. Highlights: We report population based data on CAP epidemiology including outpatients. Incidence of CAP was 9.7 per 1000 py with a hospitalisation rate of 46.5%. The 5% 30-day mortality of outpatients is driven by seniors with comorbidities. 30-day mortality of in-patients was 22% including 5% dying shortly after discharge. Comorbidities are major risk factors for incidence and mortality of CAP.